Helminth eggs in the sludge from three sewage treatment plants in Czechoslovakia - Horák, P (Folia parasitologica, 1992)
Developmental stages of 8 species of parasitic helminths were found during examination of sludge from 3 sewage treatment plants in Central Bohemia, Czechoslovakia. The eggs were comprised from Ascaris sp., Toxocara sp., Toxascaris leonina, Parascaris equorum, Enterobius vermicularis, Trichuris sp., Capillaria sp. and Hymenolepis spp. The quantity of these organisms in 100 g of dried sludge ranged between 24-105 eggs of Ascaris sp., 12-47 eggs of Toxocara sp., 0-8 eggs of Toxascaris leonina, 0-1 egg of Parascaris equorum, 2-33 eggs of Trichuris sp., 0-12 eggs of Capillaria sp., 0-46 eggs of Enterobius vermicularis and 0-49 eggs of Hymenolepis spp. Some eggs of Hymenolepis spp. and Enterobius vermicularis were structurally damaged, while some eggs of Ascaris sp. and Enterobius vermicularis contained developed larvae.
Keywords: Ascaris; Toxocara; ovum; cizopasní červi; Toxascaris; Trichuris; Animals; Capillaria; Helminths; Hymenolepis; odpadní vody; Enterobius; Ovum; zvířata; Sewage